EFFECT OF SUPPLEMENTATION OF A PROBIOTIC STRAIN ON THE PRODUCTIVE PERFORMANCE OF THE GUINEA PIG (CAVIA PORCELLUS) - Torres T., Carlos (2013)
The aim of this study was to evaluate the effect of supplementing a probiotic strainisolated from guinea pig intestinal microbiota on its performance during the growing andfattening period. A total of 80 male guinea pigs of one day old were distributed in 40experimental units. Five treatments with eight replicates per treatment were used: T1, T2,and T3 received 100, 150 and 200 ml of probiotic respectively, and T4 y T5 were thepositive and negative controls respectively. Dry matter intake (DMI), body weight gain,feed conversion ratio (FCR) and carcass yield were evaluated. T2 showed the lowestDMI (2564 g) and FCR (3.90) whereas T5 had the highest DMI (3293 g) and FCR (5.04).Body weight gain and weight and carcass yield were not affected by the probiotic. Thedietary inclusion of probiotic strains from guinea pig intestinal microbiota significantlyaffect (p<0.05) feed conversion ratio in growing and fattening guinea pigs.